Do green awards and certifications matter? Consumers’ perceptions, green behavioral intentions, and economic implications for the hotel industry: A Sri Lankan perspective - Lee, Ki-Hoon; Lee, Minwoo; Gunarathne, N. (Tourism Economics, 2019)
This study examines the effects of green or eco-friendly certificates and awards on consumers’ perceived value within the hotel industry, and the roles of consumers’ perceived value in predicting satisfaction, intention to revisit, and intention to pay a green premium. The results of partial least squares structural equation modeling analysis from a sample of 250 guests in Sri Lankan hotels showed that our unified model includes a satisfactory level of prediction power to test the hypothesized relationships. Green certificates and green awards positively affect consumers’ perceived value within the hotel industry. The findings also supported the relationship between consumers’ perceived value and satisfaction, intention to revisit, and intention to pay a green premium. The empirical findings in the context of Sri Lanka provide another important insight which confirms the positive effects of green certification and green awards on consumers’ perceived value and behavioral intentions, such as their intention to revisit and to pay a premium.
Keywords: green awards, green behavioral intention, green satisfaction, perceived green value